PEMILIHAN PENINGKATAN KAPASITAS PRODUKSI TERBAIK PADA CV. AIDRAT (AMSI) SUNAN DRAJAT LAMONGAN - Mohammad Zaki Ardiyanto (Manajemen Bisnis, 2018)
CV Aidrat Amsi was a business engaged in the production of Amdk that produce Products in the form of Galon, Bottle, and Glass. In CV product. Aidrat Amsi often comes with excess demand that does not match the amount of production. So the company is not able to meet the demand of its customers.The aim of this study was to analyze the best alternative to increase product capacity at CV Aidrat Amasi Sunan Drajat Lamongan. The results of the study showed that CV Aidrat Amsi consisted of the best three alternatives, those are gallon machine purchasing, glass, and bottle. This study also suggested that the selection of gallon machine purchasing was the best alternative due to the having the highest EMV (Expected Monetary Value).